Anticipation and futures knowledge in policy and strategy-making at the local level in Finland - Heino, Hanna (Edward Elgar Publishing, 2025)
In this chapter, I study anticipation at the municipal level in Finland. Municipalities face rapid changes in their operational environment, which increases their willingness to govern the future. Municipal strategy is a tool to anticipate the future. Anticipation helps municipalities to deal better with possible forthcoming changes as well as disruptions. The aim of this chapter is to study how attempts to anticipate the future are made by municipalities in their strategy processes. The concepts used in this chapter are anticipation, strategic thinking, and futures knowledge. Acquiring data and knowledge from the past and present, stakeholder participation, and long-term planning are part of strategic thinking and futures knowledge creation and contribute to the anticipation practices of municipalities. Based on data collected in two different surveys for the municipalities in Finland, this chapter reveals how anticipation, strategic thinking, and the creation of futures knowledge are understood and manifested in municipalities in Finland.
Future Public Governance and Global Crises: Nordic Perspectives